Distribution Characteristics and Influencing Factors of Microplastics in Urban Tap Water and Water Sources in Qingdao, China. (23rd May 2020) - Zhang, Min; Li, Jingxi; Ding, Haibing; Ding, Jinfeng; Jiang, Fenghua; Ding, Neal Xiangyu; Sun, Chengjun
Abstract: Compared with the plethora studies of microplastics in the marine environment, fewer studies have been conducted in drinking water. This study investigated the distribution and characteristics of microplastics in tap water and two major water sources in Qingdao, China. The results showed that the microplastic abundance in tap water and water sources was from 0.3 to 1.6 items/L and 0.2 to 0.7 items/L, respectively. The microplastic size ranged from 10 to 5000 μm and were black, gray, blue, and transparent. Fiber, as the dominant shape, contributed up to 99.2% of the identified microplastics. The most common polymers were rayon (48.9%) followed by polyethylene terephthalate (PET) (29.6%). Microplastics in tap water and water sources differed in size and polymer types but showed specific correlations. The analysis of Laoshan Reservoir and Jihongtan Reservoir indicated that human activities and atmospheric deposition contributed to the microplastics in the water sources. The potential risk of the microplastics was assessed by the potential risk index of the polymers. The results showed that water treatment reduced the potential risks of microplastics in tap water.